Lawrence of Arabia - Spiegel, Sam; Lean, David; Harris, Robert A.; Guiness, Alec; Quinn, Anthony; Hawkins, Jack; Ferrer, Jose; Quayle, Anthony; Rains, Claude; Kennedy, Arthur; Sharif, Omar; O'Toole, Peter (Columbia Pictures, 1962)
A historical drama re-creating the legend of a gifted soldier and true independent spirit, T. E. Lawrence, and his accomplishments in the World War I desert campaign in which he led the Arabs against the Turks in the 1920s.